Extrinsic and Intrinsic Regulation of Axon Regeneration by MicroRNAs after Spinal Cord Injury - Ping Li; Zhao-Qian Teng; Chang-Mei Liu (Neural Plasticity)
Spinal cord injury is a devastating disease which disrupts the connections between the brain and spinal cord, often resulting in the loss of sensory and motor function below the lesion site. Most injured neurons fail to regenerate in the central nervous system after injury. Multiple intrinsic and extrinsic factors contribute to the general failure of axonal regeneration after injury. MicroRNAs can modulate multiple genes’ expression and are tightly controlled during nerve development or the injury process. Evidence has demonstrated that microRNAs and their signaling pathways play important roles in mediating axon regeneration and glial scar formation after spinal cord injury. This article reviews the role and mechanism of differentially expressed microRNAs in regulating axon regeneration and glial scar formation after spinal cord injury, as well as their therapeutic potential for promoting axonal regeneration and repair of the injured spinal cord.